Boy in the striped pajamas a fable - Boyne, John (New York David Fickling Books, 2006)
Bored and lonely after his family moves from Berlin to a place called "Out-With" in 1942, Bruno, the son of a Nazi officer, befriends a boy in striped pajamas who lives behind a wire fence.
1000L
94498
Keywords: Auschwitz (Concentration camp); Auschwitz (Concentration camp); Concentration camps -- Poland; Friendship; Nazis; Holocaust, Jewish -- (1939-1945); World War -- Jews -- 1939-1945